Characterization of the complete chloroplast genome of Clinopodium chinense (Labiatae), a medicinal plant in southwest of China. Issue 2 (2nd April 2020) - Zhang, Lansheng; Zhao, Feiya; Tao, Aien
Abstract: Clinopodium chinense is a medicinal plant commonly used in southwest of China. In this study, we sequenced the complete chloroplast (cp) genome sequence of C. chinense to investigate its phylogenetic relationship in the family Labiatae. The chloroplast genome of C. chinense was 151, 989 bp in length with 37.8% overall GC content, including a large single copy (LSC) region of 83, 189 bp, a small single copy (SSC) region of 17, 642 bp and a pair of inverted repeats (IRs) of 25, 579 bp. The cp genome contained 113 genes, including 80 protein coding genes, 29 tRNA genes, and 4 rRNA genes. The phylogenetic analysis indicated Clinopodium was closely related to Mentha .